Technical paper: Environmental heat stress in football is increased in synthetic surfaces - Luis Fernando Aragón Vargas (Pensar en Movimiento)
Environmental heat stress is the result of ambient temperature, radiation, and relative humidity. During football practice on synthetic surfaces and no roof, solar radiation causes an important temperature increase of the playing surface. This technical note explains how heat stress is calculated according to the WBGT index (which does not consider playing surface temperature), and quantifies the increase in a synthetic surface compared to natural grass on the same site. Football practice should be avoided during those hours with the highest solar radiation and temperature on this type of surface.